Tear-resistant and anti-cutting new energy automobile wire harness rubber sheath and preparation method thereof

By using ethylene propylene rubber and vulcanization control agent containing multiple hindered phenol structures in the wire harness rubber sheath in new energy vehicle, the problem of wire harness sheath is solved, and the effects of tear resistance, anti-fragmentation and aging resistance are achieved, and the comprehensive performance and service life of the material are improved.

CN119798874AInactive Publication Date: 2025-04-11NINGGUO ZHENGDAO RUBBER & PLASTIC PARTS +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510287948.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the laying and use of new energy vehicle wiring harness, the rubber sheath is easily cut due to friction and collision, and the waterproof and dustproof functions are lost, resulting in high-voltage wiring harness corrosion and electrical failure, threatening vehicle safety.

Method used

Ethylene-propylene rubber is used as a polymer matrix to introduce a vulcanization control agent containing a multivariate hindered phenol structure. By regulating the free radicals during the vulcanization process, the degree of perfection of the crosslinking network is improved, thereby enhancing the mechanical properties of the material and the resistance to thermal oxygen aging.

Benefits of technology

The rubber sheath has achieved tear resistance, cut-proof and aging resistance, improved the comprehensive performance and service life of the material, and ensured the stable operation of the wiring harness in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_3
    Figure QLYQS_3
  • Figure QLYQS_4
    Figure QLYQS_4
Patent Text Reader

Abstract

The invention discloses a tear-resistant and anti-cutting new energy automobile wire harness rubber sheath and a preparation method thereof, and the sheath material comprises the following components in parts by mass: 175 parts of ethylene propylene diene monomer, 0.2-1.0 part of a vulcanizing agent, 4-8 parts of a vulcanization accelerator, 0.2-1.0 part of a vulcanization control agent, 100-150 parts of a filler, 30-50 parts of a softening agent, and 0.4-1.0 part of a scorch retarder. Wherein the vulcanization control agent is a multi-element hindered phenol compound. The rubber compound is prepared through the step-by-step open mixing technology that the ethylene propylene diene monomer, the scorch retarder and the vulcanization accelerator are subjected to melt blending, then the filling agent, the softening agent, the vulcanizing agent and the vulcanization control agent are added, then the rubber compound is subjected to vulcanization forming through an injection molding machine, and the wire harness rubber sheath is obtained and has the effects of tear resistance, cutting resistance and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer material technology and science, and specifically relates to a tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath and a preparation method thereof. Background Art

[0002] Under the trend of global energy transformation and sustainable development, new energy vehicles have become the core direction of the transformation and upgrading of the automotive industry with their advantages of low emissions and high efficiency, and their ownership has exploded in recent years. In the electrical system of new energy vehicles, high-voltage wiring harnesses, as core components, undertake the key task of transmitting high voltage and high current, providing guarantees for the vehicle's power drive, battery management and the stable operation of various high-voltage equipment. Its safety and reliability directly affect the normal operation and performance of new energy vehicles.

[0003] However, the wiring harness needs to pass through the body sheet metal structure during the laying process. During the driving of the vehicle, due to vibrations, bumps and relative displacement of components, the wiring harness will produce continuous friction and collision with the sheet metal, causing the rubber sheath to be cut.

[0004] Once the rubber sheath is cut, its waterproof and dustproof functions will fail, and impurities will invade the high-voltage wiring harness and cause corrosion, seriously affecting the normal operation of the electrical system. In addition, it also reduces the insulation performance of the high-voltage wiring harness, causing electrical faults such as short circuits and leakage, resulting in vehicle power interruption and damage to key components, seriously threatening the life safety of drivers and passengers. Therefore, it is of great significance to develop a tear-resistant and cut-resistant wiring harness rubber sheath material suitable for new energy vehicles. Summary of the invention

[0005] The invention discloses a tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath and a preparation method thereof. Ethylene propylene diene monomer rubber is used as a polymer matrix, and a vulcanization controller containing a polyhedral hindered phenol structure is introduced. The free radicals in the vulcanization process are effectively regulated by the ethylene propylene diene monomer rubber, so as to improve the perfection of the cross-linking network, thereby making the sheath material have excellent mechanical properties and heat-oxidative aging resistance, and have the effects of tear-resistant, cut-resistant and aging-resistant.

[0006] The specific plan is as follows: A tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath, wherein the rubber sheath is prepared by the following method, characterized in that, first, EPDM rubber, a scorch retarder, and a vulcanization accelerator are placed on a double-roll open mill in proportion, blended at a temperature of 90-110°C and a rotation speed of 20-50rpm for 1-3min, and then a filler is added and blended for 1-3min; then, a softener, a vulcanizer, and a vulcanization controller are added in proportion, and blended at a temperature of 90-110°C and a rotation speed of 20-50rpm for 5-10min to obtain a rubber mixture; then, the rubber mixture is placed in a rubber injection molding machine, and vulcanized at 110-170°C for 2-7min to obtain the wiring harness sheath.

[0007] The structural formula of the vulcanization control agent is , , , One or more of .

[0008] Furthermore, the mass fractions of the raw materials of the rubber sheath are: 175 parts of EPDM rubber; Vulcanizing agent 0.2-1.0 part; 4-8 parts of vulcanization accelerator; Vulcanization controller 0.2-1.0 part; Filler 100-150 parts; Softener 30-50 parts; Anti-scorch agent 0.4-1.0 part; Furthermore, the EPDM rubber has a Mooney viscosity [ML (1+4) 125°C] of 30-80, an ethylene-norbornene content of 2-8wt%, a Shore A hardness of 40-85, a tensile strength of 5-20 MPa, and an elongation at break of 200-550%; The vulcanizing agent is pre-dispersed sulfur masterbatch with a density of 1.55-2.07 g / cm 3 , sulfur content ≥80%; The vulcanization accelerator is a mixture of zinc oxide and stearic acid in a mass ratio of 10:1; The filler is a mixture of carbon black N550 and carbon black N770 in a mass ratio of 1:1; The softener is paraffin oil, with a kinematic viscosity of 5-16 mm² / s at 100°C and a paraffin content of 60-65%; The anti-scorch agent is sulfonamide, with an active content of ≥80%, a Mooney viscosity [ML(1+4)50°C]≤50, and an initial melting point of ≥108°C.

[0009] The present invention has the following beneficial effects: 1) During the vulcanization process, the vulcanization controller can generate phenoxy free radicals to participate in the vulcanization reaction. The structure of the polyhedral hindered phenol can also form new cross-linking bonds and promote the uniformity and perfection of the cross-linking network. The force can be evenly transmitted inside the material, thereby improving the comprehensive performance of the material.

[0010] 2) After the formation of phenoxy free radicals, they can capture a hydrogen atom from the polymer and form a new oxidation cycle. During long-term application, this can avoid material damage caused by aging and ensure that the material can serve stably in complex environments. DETAILED DESCRIPTION

[0011] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0012] The raw materials used in the following examples are: EPDM rubber: Mooney viscosity [ML (1+4) 125℃] is 43MU, ethylene-norbornene content is 5.5wt%, Shore A hardness is 45, tensile strength is 10MPa, elongation at break is 460%, and 4436 from ENI of Italy is selected.

[0013] Vulcanizing agent: sulfur pre-dispersed glue, S-80 from Ningbo Actmix New Materials Co., Ltd.

[0014] Vulcanization accelerator: a mixture of zinc oxide and stearic acid in a mass ratio of 10:1. The zinc oxide is HT-801 from Shandong Taixing New Materials Co., Ltd., and the stearic acid is 1820 from Dukuda Indonesia Co., Ltd.

[0015] Vulcanization controller: 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylic acid]-1,1-dimethyl}-2,4,8,10-tetraoxaspirocycloundecane, AO-80 from Nanjing Milan New Materials Co., Ltd. was selected. Butylated hydroxytoluene, MIANOX BHT from Nanjing Milan New Materials Co., Ltd. was selected. 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, MIANOX 330 from Nanjing Milan New Materials Co., Ltd. was selected.

[0016] Filler: a mixture of carbon black N550 and carbon black N770 in a mass ratio of 1:1. Carbon black N550 and carbon black N770 are selected from ORION Company of Germany.

[0017] Softener: paraffin oil, PIONIER 2058 from Qingdao Hengtai New Material Technology Co., Ltd.

[0018] Anti-scorching agent: N-phenyl-N-trichloromethylthio-benzenesulfonamide, E-80 from German Rhein Chemie is selected.

[0019] The mass fractions of the raw materials in the following examples are shown in Table 1.

[0020] Table 1 Raw materials and dosage (by mass) of rubber sheath material examples and comparative examples of new energy vehicle wiring harness Components Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 EPDM 175 175 175 175 175 175 Vulcanizing agent 0.8 0.8 0.8 0.8 0.8 0.8 Vulcanization accelerator 5.5 5.5 5.5 5.5 5.5 5.5 AO-80 0.2 1.0 0.6 0 0 0 BHT 0 0 0 0 0.6 0 330 0 0 0 0 0 0.6 N550 50 50 50 50 50 50 N770 50 50 50 50 50 50 Softener 40 40 40 40 40 40 Anti-scorch agent 0.8 0.8 0.8 0.8 0.8 0.8 Example 1

[0021] The raw materials and formula of this example are shown in Table 1, and the preparation method is carried out according to the following steps: First, EPDM rubber, scorch retarder and vulcanization accelerator are placed on a double-roll mill in proportion, blended at a temperature of 90°C and a rotation speed of 32 rpm for 2 minutes, and then filler is added and blended for 3 minutes; then softener, vulcanizer and vulcanization controller are added in proportion, blended at a temperature of 100°C and a rotation speed of 32 rpm for 10 minutes to obtain a rubber mixture; the above-mentioned rubber mixture is placed in a rubber injection molding machine and vulcanized at 165°C for 5 minutes to obtain the wiring harness sheath. Example 2

[0022] The raw materials and formula of this example are shown in Table 1, and the preparation process is the same as that of Example 1. Example 3

[0023] The raw materials and formula of this example are shown in Table 1, and the preparation process is the same as that of Example 1.

[0024] Comparative Example 1 The raw materials and formula of this comparative example are shown in Table 1, and its preparation process is the same as that of Example 1.

[0025] Comparative Example 2 The raw materials and formula of this comparative example are shown in Table 1, and its preparation process is the same as that of Example 1.

[0026] Comparative Example 3 The raw materials and formula of this comparative example are shown in Table 1, and its preparation process is the same as that of Example 1.

[0027] The main performance indicators of the sheath materials prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 2: Table 2 Performance test results of the embodiments and comparative examples performance unit Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Gel content % 82.2 86.7 92.4 70.6 79.4 73.4 hardness IRHD 40 44 50 32 35 35 Tensile Strength MPa 16.8 19.8 22.9 12.9 15.2 13.4 Elongation at break % 557 604 758 420 436 459 100℃ / 168h heat aging tensile strength change rate % -22 -15 -3 -49 -38 -27 100℃ / 168h heat aging elongation at break change rate % -46 -35 -10 -73 -62 -42 The test results are shown in Table 2. Example 3 has the best comprehensive performance.

[0028] Binary hindered phenol AO-80 can generate free radicals and participate in the vulcanization reaction, while increasing the vulcanization rate, forming a more complete cross-linking network. The force can be evenly transmitted inside the material, enhancing the mechanical properties of the material. In long-term use, it can annihilate the free radicals generated during the thermal oxidation aging process, avoid side reactions, increase the service life of the material, and have excellent comprehensive performance.

[0029] Compared with Example 3, Example 1 has a lower content of AO-80, and its regulating effect on the cross-linked network of the material is weaker. Compared with Example 3, the excessive amount of hindered phenol in Example 2 will capture the sulfur free radicals required for vulcanization, reduce the cross-linking reaction rate, and easily agglomerate in the polymer matrix, causing stress concentration and causing material damage, so the effect is lower than that of Example 3.

[0030] Compared with Example 3, Comparative Example 1 does not introduce a vulcanization control agent, making it difficult to regulate the vulcanization process and the cross-linking network of the material, resulting in uneven vulcanization and difficulty in meeting the material performance requirements.

[0031] Compared with Example 3, Comparative Example 2 introduces a small molecule monohindered phenol BHT, which has a weaker effect on capturing free radicals, making it difficult to control the cross-linking reaction process of the material and annihilate the free radicals generated by the thermal oxidation process, and is prone to migration, resulting in poor overall material performance.

[0032] Comparative Example 3 Compared with Example 3, the ternary hindered phenol 330 is introduced, which has a stronger capture effect on free radicals, can annihilate the free radicals generated in the thermal oxidation process, and improve the material's anti-aging ability. However, it also limits the progress of the vulcanization reaction, and the overall performance effect is not good.

[0033] In summary, the present invention proposes a tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath, which uses EPDM rubber as a polymer matrix, improves the vulcanization rate through the annihilation and capture of free radicals by a vulcanization control agent, and constructs a perfect cross-linking network, so that the force can be evenly transmitted inside the material, avoiding thermal oxidative aging and causing material damage, and improving the service stability of the material. The material has excellent mechanical properties and a low rate of change after thermal aging, and has tear-resistant, cut-resistant, and aging-resistant effects.

[0034] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0035] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath, characterized in that: The raw materials include by mass: 175 parts of EPDM rubber; Vulcanizing agent 0.2-1.0 part; 4-8 parts of vulcanization accelerator; Vulcanization controller 0.2-1.0 part; Filler 100-150 parts; Softener 30-50 parts; Anti-scorch agent 0.4-1.0 part; The structural formula of the vulcanization control agent is , , , One or more of .

2. According to claim 1, the tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath is characterized by: The EPDM rubber has a Mooney viscosity [ML (1+4) 125°C] of 30-80, an ethylene-norbornene content of 2-8wt%, a Shore A hardness of 40-85, a tensile strength of 5-20MPa, and an elongation at break of 200-550%; The vulcanizing agent is pre-dispersed sulfur masterbatch with a density of 1.55-2.07 g / cm 3 , sulfur content ≥80%; The vulcanization accelerator is a mixture of zinc oxide and stearic acid in a mass ratio of 10:1; The filler is a mixture of carbon black N550 and carbon black N770 in a mass ratio of 1:1; The softener is paraffin oil, with a kinematic viscosity of 5-16 mm² / s at 100°C and a paraffin content of 60-65%; The anti-scorch agent is sulfonamide, with an active content of ≥80%, a Mooney viscosity [ML(1+4)50°C]≤50, and an initial melting point of ≥108°C.

3. A method for manufacturing a tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath according to any one of claims 1-2, characterized in that: The following steps are involved: First, EPDM rubber, scorch retarder and vulcanization accelerator are placed on a double-roll open mill in proportion, blended at a temperature of 90-110°C and a rotation speed of 20-50rpm for 1-3min, and then filler is added and blended for 1-3min; then softener, vulcanizer and vulcanization controller are added in proportion, blended at a temperature of 90-110°C and a rotation speed of 20-50rpm for 5-10min to obtain a rubber mixture; the above-mentioned rubber mixture is placed in a rubber injection molding machine and vulcanized at 110-170°C for 2-7min to obtain the wiring harness sheath.

4. A tear-resistant and cut-resistant new energy vehicle wiring harness rubber sheath according to any one of claims 1 to 2 or a sheath application method obtained by the manufacturing method according to claim 3, characterized in that: The wiring harness rubber sheath is applied to new energy vehicles.

Citation Information

Patent Citations

  • Low-temperature-resistant cable material and preparation method thereof

    CN103665585A

  • Cable sheath material and preparation method thereof

    CN108148288A

  • Antibacterial TPV (thermoplastic vulcanizate) material for nurse shoes

    CN110183786A

  • Preparation method of new vulcanization system TPV material

    CN110229429A

  • Anti-aging aerial cable

    CN118852798A